Betaine Lipid Is Crucial for Adapting to Low Temperature and Phosphate Deficiency in Nannochloropsis . Issue 1 (19th March 2018) - Murakami, Hiroki; Nobusawa, Takashi; Hori, Koichi; Shimojima, Mie; Ohta, Hiroyuki
Abstract : In Nannochloropsis oceanica, betaine lipid is not only important as a surrogate for phospholipids during phosphate deficiency, but is also required for adaptation to low temperature conditions. Abstract: Diacylglyceryl- N, N, N -trimethylhomo-Ser (DGTS) is a nonphosphorous, polar glycerolipid that is regarded as analogous to the phosphatidylcholine in bacteria, fungi, algae, and basal land plants. In some species of algae, including the stramenopile microalga Nannochloropsis oceanica, DGTS contains an abundance of eicosapentaenoic acid (EPA), which is relatively scarce in phosphatidylcholine, implying that DGTS has a unique physiological role. In this study, we addressed the role of DGTS in N. oceanica . We identified two DGTS biosynthetic enzymes that have distinct domain configurations compared to previously identified DGTS synthases. Mutants lacking DGTS showed growth retardation under phosphate starvation, demonstrating a pivotal role for DGTS in the adaptation to this condition. Under normal conditions, DGTS deficiency led to an increase in the relative amount of monogalactosyldiacylglycerol, a major plastid membrane lipid with high EPA content, whereas excessive production of DGTS induced by gene overexpression led to a decrease in monogalactosyldiacylglycerol. Meanwhile, lipid analysis of partial phospholipid-deficient mutants revealed a role for phosphatidylcholine and phosphatidylethanolamine in EPA biosynthesis. These results suggest that DGTS and monogalactosyldiacylglycerol may constitute the two major pools of EPA in extraplastidic and plastidic membranes, partially competing to acquire EPA or its precursors derived from phospholipids. The mutant lacking DGTS also displayed impaired growth and a lower proportion of EPA in extraplastidic compartments at low temperatures. Our results indicate that DGTS is involved in the adaptation to low temperatures through a mechanism that is distinct from the DGTS-dependent adaptation to phosphate starvation in N. oceanica .